"Bases for Territory–Based Rural Development in The Mekong Delta, Vietnam, Can Tho" - Rodero Franganillo, Adolfo (Revista de Fomento Social, 2010)
Reseña de la obra de: AMADOR, Francisco, VAN XE, Do y otros (2009) Bases for Territory–Based Rural Development in The Mekong Delta, Vietnam, Can Tho. Agencia Española de Cooperación Internacional, Dai Hoc y ETEA, 508 pp.